2021
DOI: 10.1021/acs.est.1c04255
|View full text |Cite
|
Sign up to set email alerts
|

Precursors and Pathways Leading to Enhanced Secondary Organic Aerosol Formation during Severe Haze Episodes

Abstract: Molecular analyses help to investigate the key precursors and chemical processes of secondary organic aerosol (SOA) formation. We obtained the sources and molecular compositions of organic aerosol in PM 2.5 in winter in Beijing by online and offline mass spectrometer measurements. Photochemical and aqueous processing were both involved in producing SOA during the haze events. Aromatics, isoprene, long-chain alkanes or alkenes, and carbonyls such as glyoxal and methylglyoxal were all important precursors. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 93 publications
4
37
2
Order By: Relevance
“…In Beijing, haze episodes in winter are generally associated with a low wind speed (e.g., WS < 1.5 m s –1 herein), while clean episodes are dominated by the northern wind with high WS . In this campaign, the most polluting events occurred from March 9 to 12, featured by the maximum NR-PM 2.5 mass loading of 186.6 μg m –3 , which is close to the PM 2.5 mass concentration of 191 μg m –3 in Beijing in 2017, along with high concentrations of NO x , SO 2 , and O 3 (Figure ). In addition, high RH and weak irradiation were observed during the pollution events.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…In Beijing, haze episodes in winter are generally associated with a low wind speed (e.g., WS < 1.5 m s –1 herein), while clean episodes are dominated by the northern wind with high WS . In this campaign, the most polluting events occurred from March 9 to 12, featured by the maximum NR-PM 2.5 mass loading of 186.6 μg m –3 , which is close to the PM 2.5 mass concentration of 191 μg m –3 in Beijing in 2017, along with high concentrations of NO x , SO 2 , and O 3 (Figure ). In addition, high RH and weak irradiation were observed during the pollution events.…”
Section: Resultsmentioning
confidence: 61%
“…This can be ascribed to an increased contribution of nitrate recently in the NCP. , For example, the mean mass fractions of nitrate, ammonium, sulfate, and chloride in NR-PM 2.5 were 44.3%, 18.0%, 10.5%, and 1.2%, respectively. In particular, the mass ratio of sulfate to nitrate (0.2) was much lower than that in 2017 (1.6) and in 2018 (2.1) in Beijing. This implies a decreased aerosol acidity, which might indirectly affect SOA formation. , …”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The organonitrates formation from NO3 oxidation of biogenic or anthropogenic VOCs can affect the interactions between anthropogenic and natural emissions (He et al, 2021;Shen et al, 2021;Wang et al, 2020). Organonitrates were found to be important species contributing to SOA formation in polluted urban environment, which were enhanced under high NOx level (Zheng et al, 2021). The significant higher relative intensities of CHON compounds in winter indicated that the high NOx environment in winter promoted the formation of organonitrates and highlighted the importance of orgnonitrates for SOA control in polluted environment.…”
Section: Molecular Characteristics Of Chon Compoundsmentioning
confidence: 97%